2019
DOI: 10.1080/14397595.2019.1583711
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of baricitinib in Japanese patients with active rheumatoid arthritis with over 1.6 years median time in treatment: An integrated analysis of Phases 2 and 3 trials

Abstract: Objectives: Baricitinib is a selective oral inhibitor of JAK1/JAK2 for patients with moderately-toseverely active rheumatoid arthritis (RA). Baricitinib's safety profile in Japanese patients was evaluated using six studies (five Ph2/Ph3 trials, one long-term extension study through 01 September 2016) from an integrated database (nine RA studies). Methods: Incidence rates (IRs) or exposure-adjusted IRs (EAIRs) of adverse events (AEs) per 100 patient-years (PY) were calculated using data which included RA patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 29 publications
5
25
2
2
Order By: Relevance
“…The rate of herpes zoster seen in the 30 mg group in this study (6%) appeared to be higher than that observed in the SELECT-NEXT and SELECT-BEYOND studies (1–2%), which did not include Japanese study sites [ 14 , 21 ]. A similar trend has been observed for Japanese and Korean patients treated with tofacitinib and baricitinib vs other geographical regions [ 22 , 23 ]. The reason for the increased rate of herpes zoster in Japanese patients is unclear, although it has been suggested that genetic predisposition, regional differences in reporting and cultural or medical factors could be involved [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…The rate of herpes zoster seen in the 30 mg group in this study (6%) appeared to be higher than that observed in the SELECT-NEXT and SELECT-BEYOND studies (1–2%), which did not include Japanese study sites [ 14 , 21 ]. A similar trend has been observed for Japanese and Korean patients treated with tofacitinib and baricitinib vs other geographical regions [ 22 , 23 ]. The reason for the increased rate of herpes zoster in Japanese patients is unclear, although it has been suggested that genetic predisposition, regional differences in reporting and cultural or medical factors could be involved [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…There are also reports suggesting that RA therapies may affect immune mechanisms, which in turn could increase malignancy risk [34,35]. In our analysis, malignancy incidence rates (95% CI) per 100 PY (excluding NMSC) were numerically similar between the peficitinib groups (0.6 [0.2, 1.6]) and the placebo group (1.2 [0.2, 8.3]) in the pooled Phase 3 studies, and similar to those reported for baricitinib (0.99-1.1) [27,36] and tofacitinib (0.8 [0.6, 1.1]) [28] in Asian populations. Furthermore, patients with RA can develop MTX-associated lymphoproliferative disorders during treatment with MTX [37].…”
Section: Discussionsupporting
confidence: 77%
“…For tofacitinib and baricitinib, respectively, the reported rates of serious infections per 100 patient-years were 2.7 (including any event requiring hospitalization or parenteral antimicrobial therapy, or otherwise meeting SAE criteria) and 2.9 (including any event meeting ICH E2A criteria), respectively [19,20]. Rates of herpes zoster-related disease for tofacitinib and baricitinib were 9.2 (in patients from Japan and Korea [21]) and 6.5 (in patients from Japan [22]), and 0.9 and 0.8 for malignancies, respectively [19,20]. It should be noted, however, that drug exposure was higher in the tofacitinib (19,406 patient-years [20]) and baricitinib (6637 patient-years [19]) studies.…”
Section: Discussionmentioning
confidence: 99%